PENGARUH KERJASAMA ASEAN CHINA FREE TRADE AREA (ACFTA) TERHADAP DAYA SAING BATIK INDONESIA TAHUN 2010-2016 - Molia Ananda; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The research analyzes cooperation influence of ASEAN China Free Trade Area (ACFTA) towards Indonesian’s batik competition. One of product that now a days dominates local market is textil product of China’s batik . Batik is one of popular product of Indonesian. By ACFTA, Indonesian’s batik must compete with textil product of batik from China. The competition is controlled by price competition, where Indonesian’s batik has relative more expensive price than China’s batik. If the cooperation of ACFTA is not based by the preparation facing the import products, so it will be threat especially for Indonesian’s batik.The research teoritically has been built by using Liberalism perspective. The kind of this research is qualitative research. The data is based on secunder data through literature study such as book,website, and each other.The final result of this research is by the cooperation of ACFTA, Indonesia is able to increase batik’s product export value into the countries that are joined in this cooperation. Many ways are implemented by Indonesian government in order to increase batik’s competition to be able to compete both in local market and international market. The effort of government makes good result because every year, Indonesian’s batik export to ASEAN and China increas. Although textil import of China’s batik motived in Indonesian every year increases, but the total of batik export is getting bigger.Keywords : Batik Of Indonesia, Competitiveness, Textil Of China’s Batik motived